Water in de hedendaagse kunst. - Stork, Gijs (1992)
Brancusi, Constantin ; Puckey, Thom ; Horn, Rebecca ; Beuys, Joseph ; Merz, Marisa ; Viola, Bill ; Smithson, Robert ; Jung, Carl Gustav ; Fabre, Jan ; Schneemann, Carolee ; de Saint Phalle, Niki ; Rosenbach, Ulrike ; Fox, Terry ; Burgin, Victor ; Kemps, Niek ; Plessi, Fabrizio ; Zegveld, Peter ; Nauman, Bruce ; Cocteau, Jean ; Long, Richard ; Rinke, Klaus ; Peeters, Henk ; Issenrath, Hans Paul ; Klein, Yves ; Haacke, Hans ; Oppenheim, Dennis ; Christo ; Fend, Peter ; Gutmann, Benny KH ; Pitz, Hermann ; Dibbets, Jan ; Füglistahler, Ricardo ; Weiner, Lawrence ; Cage, John ; Brecht, George ; Schmit, Tomas
Doctoraal scriptie Kunstgeschiedenis 1991-1992
Nederlands
boek